Pola Asuh Mempengaruhi Perkembangan Anak Balita di Wilayah Posyandu Selaawi - Anna Fatwa Aistu; Nanan Sekarwana; Santun Bhekti Rahimah (Bandung Conference Series: Medical Science, 2023)
Abstract. Development can be assessed from the four domains: motor, language, socialization, and independence. One of the factors that influence children's development significantly is parenting style.Early development detection needs to be done to find deviations in development. The study aimed to analyze the relationship between parenting and development in children under five using the developmental pre-screening questionnaire (KPSP) in the Selaawi Posyandu area. The research was conducted using cross-sectional analytic observational methods. The number of samples is 75 toddlers, with the sampling technique using non-probability sampling of consecutive sampling types. The results showed that of the 75 respondents, the majority had democratic parenting styles, 47 respondents (62.7%) and authoritarian parenting styles, 28 respondents (37.3%). Based on the KPSP assessment, 60 children (80%) experienced normal development, and 15 children (20%) experienced dubious development. Of the 60 respondents, 42 respondents had democratic parenting styles, and 18 respondents had authoritarian parenting styles. Based on the results of statistical tests using the chi-square test on the research data obtained, a p-value of 0.009.The data shows that there is a relationship between parenting style and the development of toddlers. This is related to parenting methods that are not too restrictive but still pay attention to the needs and development, meet the needs of children, and communicate with children. Keywords: Child Development, Parenting, Toddlers Abstrak. Perkembangan dapat dinilai dari empat domain yaitu motorik, bahasa, sosialisasi dan kemandirian. Salah satu faktor yang mempengaruhi perkembangan anak secara signifikan adalah pola asuh. Deteksi dini perkembangan perlu dilakukan karena untuk mengetahui penyimpangan dalam perkembangan. Penelitian bertujuan untuk menganalisis hubungan antara pola asuh dengan perkembangan pada anak balita menggunakan kuesioner pra-skrining perkembangan (KPSP) di wilayah Posyandu Selaawi. Penelitian dilakukan dengann metode observasional analitik jenis cross-sectional. Jumlah sampel sebanyak 75 balita dengan teknik pengambilan sampel menggunakan non-probability sampling jenis consecutive sampling. Hasil penelitian menunjukan dari 75 responden mayoritas memiliki pola asuh demokratis 47 responden (62,7%) dan pola asuh otoriter 28 responden (37,3%). Berdasarkan penilaian KPSP terdapat 60 anak (80%) mengalami pekembangan normal dan 15 anak (20%) mengalami perkembangan meragukan. Dari 60 responden tersebut 42 responden memiliki pola asuh demokratis dan 18 responden memiliki pola asuh otoriter. Berdasarkan hasil uji statistik dengan menggunakan uji chi square pada data hasil penelitian didapatkan p-value 0,009. Data tersebut menunjukan terdapat adanya hubungan antara pola asuh orang tua dengan perkembangan anak balita. Ini berkaitan dengan cara pengasuhan orang tua yang tidak terlalu mengekang namun tetap memperhatikan kebutuhan dan perkembangan, memenuhi kebutuhan anak dan adanya komunikasi dengan anak. Kata Kunci: Balita, Perkembangan Anak, Pola Asuh